2009
DOI: 10.1017/s1751731109004042
|View full text |Cite
|
Sign up to set email alerts
|

Udder quarter milk composition at different levels of somatic cell count in cow composite milk

Abstract: Automatic milking systems have made possible the separation of high-and low-quality milk at the udder quarter level during the milking process. The aim of this study was to investigate the composition and yield of milk from individual udder quarters to determine whether deteriorated milk composition occurs in udders that are assumed to be healthy and whether quarters with high-quality milk are found in udders with high milk somatic cell count (SCC). Milk samples were collected on one occasion from 90 cows at u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 20 publications
3
53
1
11
Order By: Relevance
“…As discussed previously, the bacteriological sampling may give false-negative results, as there is a cycling of bacteria and SCC during mastitis (Forsbä ck et al, 2009). In our study, we found bacteria in four out of five cows in Group 2 and in three out of six cows in Group 3.…”
Section: Forsbä Ck Lindmark-må Nsson André N and Svennersten-sjaunjasupporting
confidence: 61%
See 2 more Smart Citations
“…As discussed previously, the bacteriological sampling may give false-negative results, as there is a cycling of bacteria and SCC during mastitis (Forsbä ck et al, 2009). In our study, we found bacteria in four out of five cows in Group 2 and in three out of six cows in Group 3.…”
Section: Forsbä Ck Lindmark-må Nsson André N and Svennersten-sjaunjasupporting
confidence: 61%
“…Findings by Forsbä ck et al (2009) further justify studying the ways in which raw milk composition differs in separate udder quarters with increased SCC at a low-to-moderate increase in cow composite SCC. In addition to analyses of gross milk composition, that is, total protein, whey protein, fat, lactose, citric acid, SCC and bacterial content, it is relevant to study the following components to gain a better understanding of how mastitis influences milk composition.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, mixing of milk from infected udders with milk from non-infected ones could not be detected by measures such as determination of SCC, proteose peptone content and % of casein, which worked well at the individual cow level as predictors of udder inflammation . Thus, the results of this and former studies Leitner et al, 2008;Forsback et al, 2009 and indicate that it is important for the dairy industry to develop analytical tools that will allow to prevent combining low-quality milk, such as milk rich in somatic cells and nitrite, with high-quality milk in order to ensure optimal yield and quality of curd from milk designated for cheese production.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies in goat, sheep and cow milk have shown that the infection status of the animal's udder (Gonzalo et al, 1994;Auldist et al, 1996;Baudry et al, 1997;Fantuz et al, 2001;Leitner et al, 2004a and2004b;Merin et al, 2008;Forsbä ck et al, 2009) and stage of lactation (Coulon, 1994;Leitner et al, 2011a) are directly related to milk quality, its composition and suitability for cheese making. Thus, some, but not all, bacteria causing mammary infection significantly reduce curd yield and quality, as well as in animals at late lactation.…”
Section: Introductionmentioning
confidence: 99%